Strategy to Increase the Competitiveness of SME’s Entreprises - Yanah, Yanah; Nakhwatunnisa, Haulah; Sukarno, Tri Amalia (Universitas Negeri Semarang, 2018)
The purpose of this study is to determine what factors can improve the competitiveness of SMEs and how big those factors affect the improvement of competitiveness of SMEs and what strategies should be done by SMEs in the face of ASEAN economics for the business actors of SMEs in Indonesia in particular in Cirebon district can compete with foreign business actors in terms of products and trained human resources so as not to be a spectator in the State itself in global competition. The method used is a survey research methods and data analysis tool used is path analysis. The population in this study is SMEs that run business activities in Cirebon regency as much as 10.975 SMEs. The sampling technique is simple random sampling, the sample size in this study as many as 100 SMEs. The research instrument used is the questionnaire. The results of the research note that funding variables, entrepreneurship training, business assistance and partnership have an effect on competitiveness in facing ASEAN economics. Among the variables that have the most influence on competitiveness are partnerships, while the variables affecting the ASEAN economy are competitiveness variables.